Territorialidade e empreendimentos econômicos solidários no Norte de Minas Gerais - Souza, Sidinéia Maria de (2015)
Transformations in global capitalism, during the last two decades, have been accompanied by changes in cultural and ethical values. There are contradictory developments which make some elements more homogeneous while deepening differences between other ones. Among such elements, the dynamics of social peripheries, urban and rural, come to the fore. Cyclical movements of capitalism, mainly in sub-national spaces, generate sui generis social mobilizations of great diversity. That is why, perhaps, there is a proliferation of studies and actions showing new methodologies of development, which highlight the role of individuals in the project of transformation of local/territorial reality by means of actions based on solidarity, reciprocity, trust and cooperation, which characterize a solidary economy. This kind of economy is an alternative model , with organized workers that are active in the process of socioeconomic transformation of the reality in which they live. The object of this thesis is to understand by means of a field research among solidary economic ventures, which perform collectively activities of production, commercialization and management, in the Northern Region of the state of Minas Gerais (in a region called sertão ) their actual capacity of planning their future and improving the socioeconomic conditions in their locality.